Temporal changes in head and neck cancer incidence in Thailand suggest changing oropharyngeal epidemiology in the region - Ilona Argirion (2019)
Copyright © 2019 American Society of Clinical Oncology. All rights reserved. PURPOSE Head and neck cancer is the sixth most common cancer in the world, and the largest burden occurs in developing countries. Although the primary risk factors have been well characterized, little is known about temporal trends in head and neck cancer across Thailand. METHODS Head and neck squamous cell carcinoma (HNSCC) occurrences diagnosed between 1990 and 2014 were selected by International Classification of Diseases (10th revision; ICD10) code from the Songkhla, Lampang, Chiang Mai, and Khon Kaen cancer registries and the US SEER program for oral cavity (ICD10 codes 00, 03-06), tongue (ICD10 codes 01-02), pharynx (ICD10 codes 09-10, 12-14), and larynx (ICD10 code 32). The data were analyzed using R and Joinpoint regression software to determine age-standardized incidence rates and trends of annual percent change (APC). Incidence rates were standardized using the Segi (1960) population. Stratified linear regression models were conducted to assess temporal trends in early-onset HNSCC across 20-year age groups. RESULTS Although overall HNSCC rates are decreasing across all registries, subsite analyses demonstrate consistent decreases in both larynx and oral cavity cancers but suggest increases in tongue cancers among both sexes in the United States (APCmen, 2.36; APCwomen, 0.77) and in pharyngeal cancer in Khon Kaen and US men (APC, 2.1 and 2.23, respectively). Age-stratified APC analyses to assess young-onset (< 60 years old) trends demonstrated increased incidence in tongue cancer in Thailand and the United States as well as in pharyngeal cancers in Khon Kaen men age 40 to 59 years and US men age 50 to 59 years. CONCLUSION Although overall trends in HNSCC are decreasing across both Thailand and the United States, there is reason to believe that the etiologic shift to oropharyngeal cancers in the United States may be occurring in Thailand.